Have advances in medical therapy for ulcerative colitis impacted surgical treatment?. Issue 2 (11th October 2022) - Kuwahara, Ryuichi; Ikeuchi, Hiroki; Horio, Yuki; Minagawa, Tomohiro; Kusunoki, Kurando; Uchino, Motoi
Abstract: Aim: The purpose of this study was to examine how the clinical characteristics, indications for surgery, and postoperative course of ulcerative colitis (UC) surgical patients changed before and after the introduction of biological agents. Methods: Patients who underwent surgery for UC at Hyogo Medical University between 2000 and 2019 were included in the study; those who underwent surgery between 2000 and 2009 were included in the early group (n = 864), and those who underwent surgery between 2010 and 2019 were included in the late group (n = 834); each study factor was retrospectively compared. Results: The mean ages at surgery (y) were 39.7 ± 15.1 y in the early group and 46.7 ± 17.8 y in the late group ( P < . 01). Antitumor necrosis factor agents were used (%) in 2 (0.2) patients in the early group and 317 (38.0) patients in the late group ( P < . 01). The number of cancer or dysplasia patients for whom surgery was indicated was significantly higher in the late group (11%/26%, P = . 01). With regard to surgery in elderly individuals, the number of elderly patients (65 y and older) undergoing surgery was significantly higher in the late group (8.0%/18.6%, P < . 01). For emergency surgery, the mortality rates were 16.7% (2/12) in the early surgery group and 15.7% (8/51) in the late surgery group ( P = . 61). Conclusion: The characteristics of UC patients requiring surgery in Japan have changed. The distribution of surgical indications changed, and the number of patients with cancer and dysplasia requiring surgery increased. The prognosis of elderly patients who underwent emergency surgery was poor. Abstract : The characteristics of UC patients requiring surgery in Japan have changed. The number of patients with cancer and dysplasia requiring surgery increased. The prognosis of older patients who underwent emergency surgery was poor.